Evaluation method of slag polymerization effect on zinc liquid surface

By evaluating the polymerization effect of zinc liquid slag, the difference between the initial relative aggregation and the experimental relative aggregation difference is solved, and the scientific evaluation and maximum effect of electromagnetic polyzinc slag is achieved Analysis of optimal parameters.

CN118134279BActive Publication Date: 2025-02-18ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410250330.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2025-02-18
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

The prior art lacks effective evaluation methods to evaluate the effect of electromagnetic separation technology in zinc pots, resulting in the impact of the surface quality of galvanized sheets.

Method used

By determining the influencing factors (frequency, current and zinc magnetic liquid level distance), select any factor as the factor to be evaluated, and the effect of polyzinc slag is evaluated using the differences in the initial relative aggregation degree and the experimental relative aggregation degree.

Benefits of technology

This method can effectively reflect the influence of various influencing factors on the electromagnetic slag pooling effect, help analyze the optimal parameters of electromagnetic slag pooling, and guide the zinc pot slag pooling on-site galvanized wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118134279B_ABST
    Figure CN118134279B_ABST
Patent Text Reader

Abstract

The present invention provides a method for evaluating the aggregation effect of zinc liquid surface slag, comprising: determining influencing factors, the influencing factors including frequency, current and zinc magnetic liquid surface distance; selecting any influencing factor as a factor to be evaluated, the factor to be evaluated has an initial value, testing with the initial value to obtain a first relative aggregation degree; adjusting only the initial value to a modified value, testing with the modified value to obtain a second relative aggregation degree; obtaining an evaluation result of the factor to be evaluated according to the initial value, the modified value, the first relative aggregation degree and the second relative aggregation degree. The evaluation result can reflect the influence of each influencing factor on the electromagnetic slag aggregation effect, help analyze the optimal parameters of electromagnetic slag aggregation, and is of great significance for guiding the zinc pot slag aggregation of the on-site galvanizing line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc liquid slag removal, and in particular to a method for evaluating the polymerization effect of zinc liquid surface slag. Background Art

[0002] The zinc pot is the core equipment of the continuous hot-dip galvanizing production line. The zinc slag produced during the galvanizing process affects the surface quality of the galvanized sheet, and in severe cases, the galvanized sheet product is scrapped. The zinc pot slag removal worker needs to perform the slag removal operation every 40 to 60 minutes. However, the ambient temperature around the zinc pot is high, the operating space is narrow, the workers' work is dangerous, and the labor intensity is high. Manual slag removal can easily cause excessive fluctuations in the liquid level and affect the surface quality of the galvanized sheet. Therefore, it is urgent to develop new technologies to reduce the labor intensity and working environment of workers, reduce excessive fluctuations in zinc liquid, and ensure the quality of galvanized sheets.

[0003] Electromagnetic separation technology uses the principle of the difference in electrical conductivity between the molten metal and the inside of the molten metal to separate inclusions in the molten metal. In the prior art, there is no absolutely effective evaluation method for evaluating the effect of electromagnetic separation technology on zinc slag, whether in the test stage or in the application of production lines.

[0004] In view of this, the present invention provides a method for evaluating the polymerization effect of zinc liquid surface slag. Summary of the invention

[0005] According to the above-mentioned shortcomings, a method for evaluating the polymerization effect of zinc liquid surface slag is provided. The invention mainly uses the initial relative aggregation, the test relative aggregation, the first relative aggregation and the second relative aggregation to obtain the evaluation results of the influencing factors, and reflects the effect of the zinc slag polymerization through the evaluation results.

[0006] The technical means adopted by the present invention are as follows:

[0007] The present invention provides a method for evaluating the polymerization effect of zinc liquid surface slag, comprising:

[0008] Determining influencing factors, wherein the influencing factors include frequency, current and zinc magnetic liquid level distance;

[0009] Selecting any of the influencing factors as a factor to be evaluated, wherein the factor to be evaluated has an initial value, and performing a test with the initial value to obtain a first relative concentration;

[0010] Only the initial value is adjusted to a modified value, and the test is performed with the modified value to obtain a second relative aggregation degree;

[0011] An evaluation result of the factor to be evaluated is obtained according to the initial value, the modified value, the first relative concentration and the second relative concentration.

[0012] Further, the test is performed with the initial value to obtain a first relative aggregation degree, comprising:

[0013] Mixing M zinc slags with N liters of zinc liquid to obtain a first mixed solution, wherein the M zinc slags are evenly distributed in the N liters of zinc liquid, the first mixed solution is placed in a first container, the liquid surface area of ​​the first mixed solution is S1, and according to the liquid surface areas of the M zinc slags and the first mixed solution, obtaining an initial relative aggregation degree of the first mixed solution;

[0014] Keeping the other influencing factors unchanged, the factor to be evaluated is the initial value, performing an aggregation operation on the first mixed solution, the orthographic projections of the M zinc residues on the liquid surface of the first mixed solution are multiple first projection points, the liquid surface of the first mixed solution includes a first area, and the first area is the minimum area that can cover all the first projection points, and obtaining the experimental relative aggregation degree of the first mixed solution according to the areas of the M zinc residues and the first area;

[0015] The first relative aggregation degree is obtained according to the initial relative aggregation degree of the first mixed solution and the test relative aggregation degree of the first mixed solution.

[0016] Further, the step of adjusting only the initial value to a modified value and conducting a test with the modified value to obtain a second relative aggregation degree comprises:

[0017] Mixing M zinc slags with N liters of zinc liquid to obtain a second mixed solution, wherein the M zinc slags are evenly distributed in the N liters of zinc liquid, placing the second mixed solution in a second container, wherein the second container is the same as the first container, and the liquid surface area of ​​the second mixed solution is S2, and obtaining an initial relative aggregation degree of the second mixed solution according to the liquid surface areas of the M zinc slags and the second mixed solution;

[0018] Keeping the other influencing factors unchanged, the factor to be evaluated is the modified value, performing an aggregation operation on the second mixed solution, the orthographic projections of the M zinc residues on the liquid surface of the second mixed solution are multiple second projection points, the liquid surface of the second mixed solution includes a second region, and the second region is the minimum region that can cover all the second projection points, and obtaining the experimental relative aggregation degree of the second mixed solution according to the areas of the M zinc residues and the second region;

[0019] The second relative aggregation degree is obtained according to the initial relative aggregation degree of the second mixed solution and the test relative aggregation degree of the second mixed solution.

[0020] Further, the evaluation result of the factor to be evaluated is obtained according to the initial value, the modified value, the first relative concentration and the second relative concentration, and is calculated in the following manner:

[0021]

[0022] Among them, Q A is the evaluation result of the factor to be evaluated, D2 is the second relative concentration, D1 is the first relative concentration, A2 is the modified value, and A1 is the initial value.

[0023] Furthermore, the initial relative aggregation degree of the first mixed solution is obtained according to the liquid surface areas of the M zinc slags and the first mixed solution, and is calculated in the following manner:

[0024]

[0025] Among them, D 初 is the initial relative aggregation degree of the first mixed solution, S1 is the liquid surface area of ​​the first mixed solution, and M is the amount of the zinc slag in the first mixed solution.

[0026] Further, the experimental relative aggregation degree of the first mixed solution is obtained according to the M zinc slags and the area of ​​the first region, and is calculated in the following manner:

[0027]

[0028] Among them, D 验 is the experimental relative aggregation degree of the first mixed solution, S2 is the area of ​​the first region, and M is the amount of the zinc slag in the first mixed solution.

[0029] Furthermore, the first relative aggregation degree is obtained according to the initial relative aggregation degree of the first mixed solution and the test relative aggregation degree of the first mixed solution, and is calculated in the following manner:

[0030]

[0031] Wherein, D1 is the first relative aggregation degree, D 初 is the initial relative aggregation degree of the first mixed solution, D 验 is the experimental relative aggregation degree of the first mixed solution.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] The method for evaluating the aggregation effect of zinc liquid surface slag provided by the present invention determines the influencing factors, including frequency, current and zinc magnetic liquid surface distance; selects any influencing factor as the factor to be evaluated, the factor to be evaluated has an initial value, tests with the initial value, and obtains a first relative aggregation degree; only adjusts the initial value to a modified value, tests with the modified value, and obtains a second relative aggregation degree; obtains the evaluation result of the factor to be evaluated according to the initial value, the modified value, the first relative aggregation degree and the second relative aggregation degree. The evaluation result can reflect the influence of each influencing factor on the electromagnetic slag aggregation effect, which is helpful to analyze the optimal parameters of electromagnetic slag aggregation, and is of great significance for guiding the zinc pot slag aggregation of the on-site galvanizing line. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0035] Figure 1 A schematic flow chart of a method for evaluating the polymerization effect of zinc liquid surface slag provided by the present invention.

[0036] Figure 2 This is a sampling schematic diagram of the first sample.

[0037] Figure 3 This is a sampling diagram for the second sample.

[0038] Figure 4 This is a metallographic side-planing zinc slag comparison diagram of the first sample 112 area and the second sample 112D area.

[0039] Figure 5 This is a metallographic side-planing zinc slag comparison diagram of the first sample 132 area and the second sample 132D area.

[0040] Figure 6 This is a metallographic side-planing zinc slag comparison diagram of the first sample 152 area and the second sample 152D area. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0042] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0043] Combination Figure 1 , Figure 1 A schematic flow chart of the method for evaluating the polymerization effect of zinc liquid surface slag provided by the present invention is provided to illustrate a specific embodiment of the method for evaluating the polymerization effect of zinc liquid surface slag provided by the present invention, comprising:

[0044] S1: Determine the influencing factors, including frequency, current and zinc magnetic liquid level distance;

[0045] S2: Select any influencing factor as the factor to be evaluated, the factor to be evaluated has an initial value, conduct a test with the initial value, and obtain a first relative aggregation degree;

[0046] S3: only adjusting the initial value to the modified value, conducting the test with the modified value, and obtaining the second relative aggregation degree;

[0047] S4: obtaining an evaluation result of the factor to be evaluated according to the initial value, the modified value, the first relative concentration and the second relative concentration.

[0048] It can be understood that the evaluation results can reflect the influence of various factors on the electromagnetic slag aggregation effect, which is helpful to analyze the optimal parameters of electromagnetic slag aggregation and is of great significance for guiding the zinc pot slag aggregation of on-site galvanizing lines.

[0049] In some optional embodiments, the test is performed with an initial value to obtain a first relative aggregation, comprising:

[0050] M zinc slags are mixed with N liters of zinc liquid to obtain a first mixed solution, the M zinc slags are evenly distributed in the N liters of zinc liquid, the first mixed solution is placed in a first container, the liquid surface area of ​​the first mixed solution is S1, and the initial relative aggregation degree of the first mixed solution is obtained according to the liquid surface areas of the M zinc slags and the first mixed solution;

[0051] Keeping other influencing factors unchanged and the factor to be evaluated as the initial value, the first mixed solution is subjected to agglomeration operation, the orthographic projections of the M zinc residues on the liquid surface of the first mixed solution are multiple first projection points, the liquid surface of the first mixed solution includes a first region, and the first region is the minimum region that can cover all the first projection points, and the experimental relative aggregation degree of the first mixed solution is obtained according to the areas of the M zinc residues and the first region;

[0052] The first relative aggregation degree is obtained according to the initial relative aggregation degree of the first mixed solution and the experimental relative aggregation degree of the first mixed solution.

[0053] In some optional embodiments, only the initial value is adjusted to the modified value, and the test is performed with the modified value to obtain the second relative aggregation degree, including:

[0054] M zinc slags are mixed with N liters of zinc liquid to obtain a second mixed solution, the M zinc slags are evenly distributed in the N liters of zinc liquid, the second mixed solution is placed in a second container, the second container is the same as the first container, the liquid surface area of ​​the second mixed solution is S2, and the initial relative aggregation degree of the second mixed solution is obtained according to the liquid surface areas of the M zinc slags and the second mixed solution;

[0055] Keeping other influencing factors unchanged, the factor to be evaluated is a modified value, performing an aggregation operation on the second mixed solution, the orthographic projections of the M zinc residues on the liquid surface of the second mixed solution are multiple second projection points, the liquid surface of the second mixed solution includes a second region, and the second region is the minimum region that can cover all the second projection points, and the experimental relative aggregation degree of the second mixed solution is obtained according to the areas of the M zinc residues and the second region;

[0056] The second relative aggregation degree is obtained according to the initial relative aggregation degree of the second mixed solution and the experimental relative aggregation degree of the second mixed solution.

[0057] In some optional embodiments, the evaluation result of the factor to be evaluated is obtained according to the initial value, the modified value, the first relative concentration and the second relative concentration, and is calculated in the following manner:

[0058]

[0059] Among them, Q A is the evaluation result of the factor to be evaluated, D2 is the second relative aggregation, D1 is the first relative aggregation, A2 is the modified value, and A1 is the initial value.

[0060] In some optional embodiments, the initial relative aggregation degree of the first mixed solution is obtained according to the liquid surface areas of the M zinc slags and the first mixed solution, and is calculated in the following manner:

[0061]

[0062] Among them, D初 is the initial relative aggregation degree of the first mixed solution, S1 is the liquid surface area of ​​the first mixed solution, and M is the amount of zinc slag in the first mixed solution.

[0063] In some optional embodiments, the experimental relative aggregation degree of the first mixed solution is obtained according to the M zinc slags and the area of ​​the first region, and is calculated in the following manner:

[0064]

[0065] Among them, D 验 is the experimental relative aggregation degree of the first mixed solution, S2 is the area of ​​the first region, and M is the amount of zinc slag in the first mixed solution.

[0066] In some optional embodiments, the first relative aggregation is obtained according to the initial relative aggregation of the first mixed solution and the experimental relative aggregation of the first mixed solution, and is calculated in the following manner:

[0067]

[0068] Among them, D1 is the first relative aggregation degree, D 初 is the initial relative aggregation degree of the first mixed solution, D 验 is the experimental relative aggregation degree of the first mixed solution.

[0069] In some optional embodiments, referring to Figures 2 to 6 , Figure 2 A sampling diagram of the first sample is shown in FIG. Figure 3 A sampling diagram of the second sample is shown in FIG. Figure 4 This is a metallographic side planing zinc slag comparison diagram of the first sample 112 area and the second sample 112D area. Figure 5 This is a metallographic side planing zinc slag comparison diagram of the first sample 132 area and the second sample 132D area. Figure 6 This is a metallographic side planing zinc slag comparison diagram of the first sample 152 area and the second sample 152D area. The first sample is a sample formed by placing a mixed solution of zinc slag and zinc liquid in a container and solidifying. After the first sample is heated and melted and subjected to electromagnetic slag gathering treatment, it solidifies again in the container to form the second sample. Figure 2 and Figure 3 , the first sample is divided into the left part, the middle part and the right part in the direction of the traveling wave, and samples are taken from the 112D area on the left, the 132D area in the middle and the 152 area on the right. Similarly, samples are taken from the 112 area, the 132 area and the 152 area of ​​the second sample. The 112 area corresponds to the 112D area, the 132 area corresponds to the 132D area, and the 152 area corresponds to the 152D area. Taking the electromagnetic slag gathering treatment to push the zinc slag to the edge of the container as an example, refer to Figures 4 to 6 ,exist Figures 4 to 6In the figure, the upper picture is the metallographic side planing picture of the first sample, and the lower picture is the metallographic side planing picture of the second sample. It can be seen that the amount and area of ​​zinc slag in areas 112 and 152 have increased significantly, while the amount and area of ​​zinc slag in area 132 have decreased significantly, and the shape of the zinc slag is relatively regular and concentrated, which proves the effectiveness of electromagnetic slag treatment.

[0070] Furthermore, referring to Table 1, the influencing factors of electromagnetic slag aggregation treatment are analyzed.

[0071] First, the effect of frequency on slag aggregation was analyzed. The relative aggregation values ​​corresponding to the four frequency levels of 5Hz, 10Hz, 15Hz, and 20Hz were selected with a current of 50A. Through data analysis, it was found that the relative aggregation increased approximately linearly with the increase of frequency. The maximum relative aggregation value was 11.4% in the 11th test, and the minimum relative aggregation value was 3.0% in the 1st test.

[0072] Then, the influence of current on the slag aggregation effect was analyzed. The relative aggregation values ​​corresponding to the 20Hz frequency and the four current levels of 50A, 100A, 150A, and 200A were selected. Through data analysis, it was found that with the increase of current, the relative aggregation showed an approximately linear increase, but the linear slope increased from 0.00066 to 0.00184, indicating that the influence of large current on the relative aggregation is greater. The maximum relative aggregation value was 30.6% in the 20th test, and the minimum relative aggregation value was 11.1% in the 10th test.

[0073] Finally, the influence of the zinc magnetic liquid surface distance on the slag aggregation effect was analyzed. The current was 300A and the frequency was 20Hz. The relative aggregation values ​​corresponding to the three levels of zinc magnetic liquid surface distance were 125mm, 180mm, and 240mm. Through data analysis, it was found that with the increase of the zinc magnetic liquid surface distance, the relative aggregation showed an approximately linear decrease. The maximum relative aggregation value was 30.6% in the 20th test, and the minimum relative aggregation value was 17.4% in the 27th test.

[0074] In other words, frequency, current and zinc-magnetic liquid surface distance are all factors affecting the slag aggregation effect.

[0075] Table 1. Experimental basic data table

[0076]

[0077] Table 1. Experimental basic data table

[0078] 16 200 20 125 0.15 666 0.1248 801 20.2 17 200 20 125 0.15 666 0.1245 803 20.6 18 200 20 125 0.15 666 0.1242 805 21 19 300 20 125 0.15 666 0.1158 863 29.6 20 300 20 125 0.15 666 0.1149 870 30.6 21 300 20 125 0.15 666 0.1156 865 29.8 22 300 20 180 0.075 1333 0.0593 1686 26.4 23 300 20 180 0.075 1333 0.0589 1695 27.1 24 300 20 180 0.075 1333 0.0595 1679 25.9 25 300 20 240 0.15 666 0.1271 787 18.1 26 300 20 240 0.15 666 0.1258 795 19.3 27 300 20 240 0.15 666 0.1279 782 17.4

[0079] The known influencing factors are frequency, current and zinc-magnetic liquid surface distance. A comprehensive analysis showed that when the frequency is 20 Hz and the current is 300 A, that is, the online operating capacity of the equipment, and the zinc-magnetic liquid surface distance is 125 mm, the zinc slag aggregation effect is best. The surface slag in the zinc ingot shows the characteristic of gathering towards the edge, while the zinc slag in the middle of the zinc ingot is significantly less. During the experiment, the zinc liquid level fluctuation is within a reasonable range and does not exceed 0.5 mm. When the zinc-magnetic liquid surface distance exceeds 180 mm, the zinc slag aggregation effect is not obvious.

[0080] In some optional embodiments, referring to Table 2 and Table 3, the minimum relative aggregation influence factor Q f3 The maximum value is 0.0076, which means that when the frequency increases by the same unit, the larger the basic value of the frequency is, the greater the effect on the aggregation of zinc slag is.

[0081] Minimum relative aggregation factor Q f1 The minimum is 0.0026, which means that when the frequency increases by the same unit, the smaller the basic value of the frequency is, the smaller the effect on the aggregation of zinc slag is, and the less obvious the aggregation effect is.

[0082] Maximum relative aggregation factor Q A3 The maximum is 0.1, which means that when the current increases by the same unit, the larger the basic value of the current is, the greater the effect on the aggregation of zinc slag is.

[0083] Maximum relative aggregation factor Q A2 The minimum is 0.053, which means that when the current increases by the same unit, when the basic value of the current is between 100A and 150A, the effect on the aggregation of zinc slag is smaller and the aggregation effect is less obvious.

[0084] Table 2. Corresponding table of line slopes of 50A current variable frequency slag graph

[0085] project <![CDATA[Q f1 ]]> <![CDATA[Q f2 ]]> <![CDATA[Q f3 ]]> <![CDATA[Maximum relative aggregation degree D 相对max > 0.0038 0.006 0.0058 <![CDATA[Minimum relative aggregation degree D 相对min > 0.0026 0.006 0.0076 <![CDATA[Intermediate relative aggregation degree D 相对mid > 0.0036 0.006 0.0062

[0086] Table 3. Corresponding table of slope of dangerous section of 20Hz frequency variable current slag accumulation diagram

[0087] project <![CDATA[Q A1 ]]> <![CDATA[Q A2 ]]> <![CDATA[Q A3 ]]> <![CDATA[Maximum relative aggregation degree D 相对max > 0.078 0.053 0.1 <![CDATA[Minimum relative aggregation degree D 相对min > 0.054 0.064 0.094 <![CDATA[Intermediate relative aggregation degree D 相对mid > 0.066 0.061 0.092

[0088] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.

[0089] In the above embodiments of the present invention, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for evaluating the polymerization effect of zinc liquid surface slag, characterized in that: include: Determining influencing factors, wherein the influencing factors include frequency, current and zinc magnetic liquid level distance; Selecting any of the influencing factors as a factor to be evaluated, wherein the factor to be evaluated has an initial value, and performing a test with the initial value to obtain a first relative concentration; Only the initial value is adjusted to a modified value, and the test is performed with the modified value to obtain a second relative aggregation degree; Obtaining an evaluation result of the factor to be evaluated according to the initial value, the modified value, the first relative concentration and the second relative concentration; The step of conducting the test with the initial value to obtain a first relative aggregation degree comprises: Mixing M zinc slags with N liters of zinc liquid to obtain a first mixed solution, wherein the M zinc slags are evenly distributed in the N liters of zinc liquid, the first mixed solution is placed in a first container, the liquid surface area of ​​the first mixed solution is S1, and according to the liquid surface areas of the M zinc slags and the first mixed solution, obtaining an initial relative aggregation degree of the first mixed solution; Keeping the other influencing factors unchanged, the factor to be evaluated is the initial value, performing an aggregation operation on the first mixed solution, the orthographic projections of the M zinc residues on the liquid surface of the first mixed solution are multiple first projection points, the liquid surface of the first mixed solution includes a first area, and the first area is the minimum area that can cover all the first projection points, and obtaining the experimental relative aggregation degree of the first mixed solution according to the areas of the M zinc residues and the first area; Obtaining the first relative aggregation degree according to the initial relative aggregation degree of the first mixed solution and the test relative aggregation degree of the first mixed solution; The step of only adjusting the initial value to a modified value and conducting a test with the modified value to obtain a second relative aggregation degree comprises: Mixing M zinc slags with N liters of zinc liquid to obtain a second mixed solution, wherein the M zinc slags are evenly distributed in the N liters of zinc liquid, placing the second mixed solution in a second container, wherein the second container is the same as the first container, and the liquid surface area of ​​the second mixed solution is S2, and obtaining an initial relative aggregation degree of the second mixed solution according to the liquid surface areas of the M zinc slags and the second mixed solution; Keeping the other influencing factors unchanged, the factor to be evaluated is the modified value, performing an aggregation operation on the second mixed solution, the orthographic projections of the M zinc residues on the liquid surface of the second mixed solution are multiple second projection points, the liquid surface of the second mixed solution includes a second region, and the second region is the minimum region that can cover all the second projection points, and obtaining the experimental relative aggregation degree of the second mixed solution according to the areas of the M zinc residues and the second region; The second relative aggregation degree is obtained according to the initial relative aggregation degree of the second mixed solution and the test relative aggregation degree of the second mixed solution.

2. The method for evaluating the polymerization effect of zinc liquid surface slag according to claim 1, characterized in that: The evaluation result of the factor to be evaluated is obtained according to the initial value, the modified value, the first relative concentration and the second relative concentration, and is calculated in the following manner: Among them, Q A is the evaluation result of the factor to be evaluated, D2 is the second relative concentration, D1 is the first relative concentration, A2 is the modified value, and A1 is the initial value.

3. The method for evaluating the polymerization effect of zinc liquid surface slag according to claim 1, characterized in that: The initial relative aggregation degree of the first mixed solution is obtained according to the liquid surface areas of the M zinc slags and the first mixed solution, and is calculated in the following manner: Among them, D 初 is the initial relative aggregation degree of the first mixed solution, S1 is the liquid surface area of ​​the first mixed solution, and M is the amount of the zinc slag in the first mixed solution.

4. The method for evaluating the polymerization effect of zinc liquid surface slag according to claim 1, characterized in that: The experimental relative aggregation degree of the first mixed solution is obtained according to the M zinc slags and the area of ​​the first region, and is calculated in the following manner: Among them, D 验 is the experimental relative aggregation degree of the first mixed solution, S2 is the area of ​​the first region, and M is the amount of the zinc slag in the first mixed solution.

5. The method for evaluating the polymerization effect of zinc liquid surface slag according to claim 1, characterized in that: The first relative aggregation degree is obtained according to the initial relative aggregation degree of the first mixed solution and the experimental relative aggregation degree of the first mixed solution, and is calculated in the following manner: Wherein, D1 is the first relative aggregation degree, D 初 is the initial relative aggregation degree of the first mixed solution, D 验 is the experimental relative aggregation degree of the first mixed solution.